2018
DOI: 10.1038/s41598-018-32145-3
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of entanglement and spin state transfer via quantum chains of atomic spins at large separations

Abstract: Several recent experiments have shown that long-range exchange interactions can determine collective magnetic ground states of nanostructures in bulk and on surfaces. The ability to generate and control entanglement in a system with long-range interaction will be of great importance for future quantum technology. An important step forward to reach this goal is the creation of entangled states for spins of distant magnetic atoms. Herein, the generation of long-distance entanglement between remote spins at large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Similarly, entanglement improvement in quantum spin system is another crucial site of work. While there are methods of improving long-distance entanglement such as the use of quantum mediators -for example, sets of antiferromagnetically coupled spin dimers [28] -we focus on the use of control field configurations [29][30][31]. The use of control fields has a dual advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, entanglement improvement in quantum spin system is another crucial site of work. While there are methods of improving long-distance entanglement such as the use of quantum mediators -for example, sets of antiferromagnetically coupled spin dimers [28] -we focus on the use of control field configurations [29][30][31]. The use of control fields has a dual advantage.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental realization of spin chains is based on systems such as optical lattices, trapped ions, and solid state setups [5]. Quantum spin chains have been used to: achieve entanglement and state transfer via chains of atomic spins at large separations [6], achieve conditional state transfer which realizes a quantum spin transistor [1], engineer spin couplings in elemental superconductors [7], and realize long-distance entanglement between spins in antiferromagnetic quantum spin chains [8]. Among other things, achieving entanglement between spins is imperative when it comes to quantum information applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown in [15] that the natural dynamics of a single spin chain are able to sustain the generation of two pairs of Bell states, possibly shared between a sender and a receiver, which can in turn enable two-qubit teleportation. Spin chains have also been proposed to act as quantum mediators to achieve perfect long-range entanglement between remote spins on bulk and on surfaces of magnetic nanostructures [6]. Experimentally, long distance entanglement between spins in antiferromagnetic quantum spin chains has been demonstrated in [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the amount of fidelity is equal to 1 for a four-spin ring which denotes such a ring can provide a perfect quantum communication [4]. In addition, magnetic spin chains meet many other requirements in several inspiring technologies for the processing of quantum information [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%